Konseling Rational Emotive Behavioral dengan Teknik Pencitraan untuk Meningkatkan Resiliensi Mahasiswa Berstatus Sosial Ekonomi Lemah - Mashudi, Esya Anesty (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This research aims to find out the effectiveness of rational emotive behavioral counseling through imagery technique as an effort to enhance the psychological resilience of the students with low socio-economy status. This research used quantitative-qualitative approach with mixed research method. Quasi experimental design to test the effectiveness of the intervention useing non-equivalentpretest-posttest control group design. It was conducted in Universitas Pendidikan Indonesiain Serang Regional Campus by 160 students as participants who were selected using purposive sampling technique. The data was collected by using Adolescenceâs Resilience Scale and Activity Journal. The result indicated that rational emotive behavioral counseling through imagery technique proved empirically effective to enhance the resilience of the students with low socio-economy status. Based on t-test from pretest and posttest experiment group result, it can be seen that H0 was rejected (t count = 8.152 and t table=1.760.) This research can be used as a reference in improving the resilience of students with low socio-economic status by the guidance and counseling sevice unit in universities, lecturers, counselors at the college to improve low economic status studentsâ resilience.